Mutations in the AXIN1 gene in advanced prostate cancer. - Yardy, G; Bicknell, D; Wilding, J; Bartlett, S; Liu, Y; Winney, B; Turner, G; Brewster, S; Bodmer, W (2009)
BACKGROUND: The Wnt signalling pathway directs aspects of embryogenesis and is thought to contribute to maintenance of certain stem cell populations. Disruption of the pathway has been observed in many different tumour types. In bowel, stomach, and endometrial cancer, this is usually due to mutation of genes encoding Wnt pathway components APC or beta-catenin. Such mutations are rare in hepatocellular carcinomas and medulloblastomas with Wnt pathway dysfunction, and there, mutation in genes for other Wnt molecules, such as Axin, is more frequently found. OBJECTIVE: Although evidence of abnormal activation of the Wnt pathway in prostate cancer has been demonstrated by several groups, APC and beta-catenin mutations are infrequent. We sought mutations in genes encoding Wnt pathway participants in a panel of prostate cancer clinical specimens and cell lines. DESIGN, SETTING, AND PARTICIPANTS: DNA was obtained from 49 advanced prostate cancer specimens using laser microdissection followed by whole genome amplification and 8 prostate cancer cell lines. MEASUREMENTS: The DNA samples were screened for mutations in the genes encoding APC, beta-catenin, and Axin. The subcellular distribution of beta-catenin expression was assessed in the clinical specimens using immunohistochemistry. RESULTS AND LIMITATIONS: Abnormal patterns of beta-catenin expression, suggesting Wnt pathway dysregulation, were observed in 71% of specimens. One APC mutation, two beta-catenin gene mutations, and 7 DNA sequence variations in the Axin gene were detected. Four different Axin polymorphisms were also found in the cell lines. The study does not provide definite evidence that the observed sequence changes alter protein function, promoting neoplasia, but the potential functional relevance of these variants is discussed. CONCLUSIONS: These data contribute to our understanding of the role of Wnt dysregulation in prostatic tumourigenesis and support the current interest in the pathway as a therapeutic target. Of particular interest, we identified three new potentially functionally relevant AXIN1 mutations.